A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component
By using a combination of zinc chloride, zinc acetate and acetic acid in the hot-dip galvanizing process, and adding cyclodextrin, combined with chromium-free passivation liquid, uneven coating, low adhesion and corrosion resistance, The problems of severe smoke and high zinc loss have achieved the preparation of hot-dip galvanized iron components with high adhesion and corrosion resistance.
Patent Information
- Application Number
- CN202411135306.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-19
AI Technical Summary
In the existing hot-dip galvanizing process, the film-forming performance of conventional auxiliary plating solvents is poor, resulting in uneven coating, reduced adhesion and corrosion resistance, and there are problems such as severe smoke and high zinc loss.
The combination of zinc chloride, zinc acetate and acetic acid is used as the plating solvent, combined with a small amount of cyclodextrin, to form a good inclusion compound and film-forming adhesion effect, improve the uniformity of the plating layer and corrosion resistance, and pass through chromium-free passivation liquid Further improve the corrosion resistance of iron components.
It significantly improves the adhesion and corrosion resistance of the galvanized layer, reduces zinc loss and smoke generation, and improves the uniformity of the plating layer and the environmental protection of the process.
Smart Images

Figure BDA0004999236310000081 
Figure BDA0004999236310000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-dip galvanizing, and in particular relates to a method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Background Art
[0002] Hot-dip galvanizing is an effective method for metal corrosion protection, mainly used in metal structural facilities in various industries. The rust-free workpiece is immersed in molten zinc liquid at about 500℃, so that a zinc layer adheres to the surface of the workpiece, thereby achieving the purpose of corrosion protection.
[0003] The hot-dip galvanizing process mainly includes four basic steps: pre-plating surface treatment, plating treatment, hot-dip plating and post-plating treatment. The process is as follows: pre-plating parts alkaline degreasing - acid washing and rust removal - water washing and impurity removal - dip plating solvent - drying - hot-dip plating - post-plating treatment - finished products. Among them, dip plating solvent treatment is an important part of the process, and it is a key step to improve the quality of the coating, prevent missed plating, and improve adhesion and corrosion resistance.
[0004] At present, the main plating solvent used in the hot-dip galvanizing process is a composite aqueous solution of zinc chloride and ammonium chloride. After the workpiece is immersed in the composite solvent of zinc chloride and ammonium chloride, a composite crystal film is formed on the surface, which helps to reduce the oxidation of the workpiece surface before immersion in the zinc pool. The molten ZnCl2 salt floats on the surface of the zinc pool and has the effect of dissolving metal oxide molecules. At the same time, the crystal film formed by ammonium chloride on the surface of the workpiece will decompose when it is immersed in the zinc pool, and the released HC1 gas will corrode the oxides formed on the surface of the zinc pool and the residual oxides on the surface of the workpiece, so as to ensure better contact and reaction between zinc and iron, and obtain a good zinc coating.
[0005] However, there are still some problems in the practical application of the composite plating solvent of conventional zinc chloride and ammonium chloride. First, the composite plating solvent of zinc chloride and ammonium chloride has poor film-forming performance, which causes uneven adhesion of the plating solvent due to gravity after the workpiece is taken out of the plating solvent. The composite crystal film formed in the subsequent drying process has poor uniformity, and is prone to leak plating or uneven coating, resulting in reduced adhesion and corrosion resistance. Second, the composite crystal film containing ammonium chloride will decompose into NH3 and HCl gas at high temperature after being immersed in the zinc pool, producing a large amount of smoke and dust, affecting the operating environment and surrounding ecological environment of the galvanizing process. Third, the HCl produced by the decomposition of ammonium chloride corrodes the iron component matrix at a high speed at high temperature, gradually increasing the ferrous ion content in the plating agent, and reacting with the zinc liquid to produce a large amount of zinc ash and zinc slag during the galvanizing process, resulting in a significant increase in zinc loss. Therefore, the development of a plating solvent with better plating effect, more environmental protection and lower zinc loss is a technical problem that needs to be solved by those skilled in the art.
[0006] CN 110172658 A discloses a hot-dip galvanizing auxiliary agent, which comprises the following components: 110-200 g / L zinc chloride, 20-96 g / L potassium chloride, and 20-48 g / L sodium chloride, wherein the weight ratio of potassium chloride to sodium chloride is 1:1-2, and the total weight of potassium chloride and sodium chloride is 40-70% of the weight of zinc chloride. Potassium chloride and sodium chloride are used to replace ammonium chloride to solve the problem of serious smoke generation in the hot-dip galvanizing industry. However, the plating auxiliary solvent using potassium chloride and sodium chloride has limited ability to dissolve metal oxides, which is not conducive to obtaining a good zinc coating. CN 101575691 A discloses a multifunctional plating auxiliary agent for hot-dip plating, which is composed of zinc chloride, sodium chloride, potassium chloride, sodium fluoride and a composite surfactant synthesized from fluorocarbon and hydrocarbon surfactants. Similarly, sodium chloride and potassium chloride are used to partially replace ammonium chloride to reduce the amount of smoke generated on the surface of the zinc bath during hot-dip plating. CN 112126876 A discloses a plating aid solution, which includes ammonium chloride, zinc chloride, water-soluble oligomeric chitosan, ethanol, trimethylpentanol hydroxyethyl ether and other ingredients. The water-soluble oligomeric chitosan binds zinc ions in the solution, degrades in an acidic environment, and slowly releases zinc ions, thereby maintaining a stable zinc ion concentration in the plating aid solution and avoiding excessive concentration, thereby ensuring uniform plating aid. However, the solution cannot solve the serious acid mist problem caused by ammonium chloride and the problem of high zinc loss. Summary of the invention
[0007] In view of the shortcomings and deficiencies of the above prior art, the object of the present invention is to provide a method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. The preparation method of the present invention uses a specific plating-assisting solvent to perform hot-dip plating on the iron component, which can significantly improve the adhesion of the galvanized layer and the corrosion resistance of the iron component, and can effectively reduce the serious acid mist problem caused by ammonium chloride and the problem of high zinc loss.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0010] The iron component which has been subjected to alkaline degreasing treatment, pickling and rust removal treatment, and water rinsing treatment is immersed in a plating solvent, and the plating treatment is carried out at a temperature of 40 to 70°C for 30 seconds to 5 minutes, and then taken out and dried, and then immersed in a hot-dip galvanizing solution for hot-dip plating, and then taken out and cooled to obtain a high-adhesion and corrosion-resistant hot-dip galvanized iron component;
[0011] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0012] Zinc chloride 80-150g / L, zinc acetate 60-120g / L, acetic acid 10-30g / L, cyclodextrin 5-20g / L.
[0013] Preferably, the alkaline washing and degreasing treatment refers to spraying the iron component with an alkaline degreasing agent solution at 20 to 60° C. for alkaline washing and degreasing treatment.
[0014] Preferably, the pickling and rust removal treatment refers to immersing the iron component in a 20-50 g / L dilute hydrochloric acid solution for 5-15 minutes.
[0015] Preferably, the drying refers to drying at 100-150° C. for 2-10 min.
[0016] Preferably, the hot-dip galvanizing liquid is pure zinc liquid or zinc liquid added with trace elements; the trace elements are at least one of rare earth elements, aluminum, silicon, and tin; and the added amount of the trace elements is 0.1% to 5% of the mass of the zinc liquid.
[0017] Preferably, the hot-dip coating temperature is 450-550°C.
[0018] Preferably, the hot-dip galvanized iron component is further immersed in a chromium-free passivation solution for passivation treatment to obtain a high-adhesion, corrosion-resistant hot-dip galvanized iron component.
[0019] Furthermore, the chromium-free passivation solution is an aqueous solution containing the following concentration components:
[0020] Water-based resin film-forming agent 5% to 15%, silica sol (calculated as SiO2 content) 3% to 8%, nitrate 2% to 5%, corrosion inhibitor 2% to 5%, organic acid 1% to 5%, silane coupling agent 0.5% to 2%.
[0021] Preferably, the water-based resin film-forming agent is a water-based acrylic resin, a water-based polyurethane, a water-based silicone resin or a water-based epoxy resin.
[0022] Preferably, the nitrate is at least one of sodium nitrate, potassium nitrate, aluminum nitrate, magnesium nitrate, nickel nitrate, cobalt nitrate and cerium nitrate.
[0023] Preferably, the corrosion inhibitor is a phosphate corrosion inhibitor or a borate corrosion inhibitor.
[0024] Preferably, the organic acid is at least one of phytic acid, citric acid, tartaric acid, acetic acid, propionic acid and butyric acid.
[0025] Preferably, the silane coupling agent is at least one of an alkyl silane coupling agent, a vinyl silane coupling agent, an epoxy silane coupling agent, and an amino silane coupling agent.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The plating solvent of the present invention adopts a combination of zinc chloride, zinc acetate and acetic acid as the main rust-removing functional component. Zinc chloride has a good effect of dissolving metal oxide molecules during hot-dip plating, while zinc acetate and acetic acid can further corrode the oxides formed on the surface of the zinc pool and the residual oxides on the surface of the iron component during hot-dip plating, thereby improving the surface condition of the iron component before hot-dip plating and obtaining a better zinc coating. At the same time, the combination of zinc acetate and acetic acid can significantly reduce the amount of smoke generated compared to NH3 and HCl gases generated by the decomposition of ammonium chloride at high temperature, and the combination of zinc acetate and acetic acid can reduce the corrosion of the iron component matrix compared to HCl, reduce the ferrous ion content, and achieve the technical effect of reducing zinc loss.
[0028] (2) The plating solvent of the present invention uses a small amount of cyclodextrin as an auxiliary film-forming aid, which can form a good and uniform inclusion complex with zinc chloride, zinc acetate and acetic acid; at the same time, the polyhydroxy structure of cyclodextrin has a hydrogen bonding effect and a higher binding force with the iron oxide zone, thereby forming a certain enrichment effect in the oxide zone, which can better dissolve and corrode the iron oxide, and reduce the corrosion of the iron components in the unoxidized zone, thereby achieving a better rust removal effect and reducing the ferrous ion content. In addition, the film-forming adhesion effect of cyclodextrin itself can reduce the uneven adhesion of the plating solvent caused by gravity, and can significantly improve the uniformity of the composite crystal film formed during the drying process, thereby improving the hot-dip galvanizing effect.
[0029] (3) The preparation method of the present invention further uses a chromium-free passivation solution of a specific composition to passivate the hot-dip galvanized iron component, which can further improve its corrosion resistance. The chromium-free passivation solution used is completely chromium-free, which has the advantage of being green and environmentally friendly. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0031] Example 1
[0032] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0033] The iron components were sprayed with 40°C alkaline degreasing agent solution (BONDERITE C-AK 338L) for alkaline washing and degreasing treatment, rinsed with water and immersed in 35g / L dilute hydrochloric acid solution for 10 minutes for pickling and rust removal, rinsed with water and immersed in a plating solvent for plating at 55°C for 90s, taken out and dried at 120°C for 3min, then immersed in 490°C hot-dip galvanizing liquid (composed of 0.18wt% aluminum and 98.2wt% zinc) for hot-dip plating for 1min until zinc ash and carbides floated on the surface of the zinc liquid, taken out and cooled in a water bath to obtain high adhesion and corrosion-resistant hot-dip galvanized iron components.
[0034] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0035] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, cyclodextrin 10g / L.
[0036] The preparation method of the plating-assisting solvent is as follows: cyclodextrin is added into water to be uniformly dissolved, and then zinc chloride, zinc acetate and acetic acid are added in sequence to be stirred and uniformly dissolved to obtain the plating-assisting solvent.
[0037] Example 2
[0038] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0039] The iron components were sprayed with alkaline degreasing agent solution (BONDERITE C-AK 338L) at room temperature for alkaline washing and degreasing treatment, rinsed with water, immersed in 50g / L dilute hydrochloric acid solution for 5 minutes for pickling and rust removal, rinsed with water, immersed in a plating solvent for plating at 45°C for 5 minutes, taken out and dried at 120°C for 3 minutes, then immersed in 480°C hot-dip galvanizing liquid (composed of pure zinc) for hot dip plating for 1 minute until zinc ash and carbide floated on the surface of the zinc liquid, taken out and cooled in a water bath to obtain high adhesion and corrosion-resistant hot-dip galvanized iron components.
[0040] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0041] Zinc chloride 150g / L, zinc acetate 60g / L, acetic acid 10g / L, cyclodextrin 5g / L.
[0042] The preparation method of the plating solvent is the same as that in Example 1.
[0043] Example 3
[0044] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0045] The iron components were sprayed with 60°C alkaline degreasing agent solution (BONDERITE C-AK 338L) for alkaline washing and degreasing treatment, rinsed with water and immersed in 20g / L dilute hydrochloric acid solution for 15 minutes for pickling and rust removal, rinsed with water and immersed in a plating solvent for 1 minute at 65°C, taken out and dried at 120°C for 3 minutes, and then immersed in 500°C hot-dip galvanizing liquid (composed of 0.25wt% silicon and 97.5wt% zinc) for hot-dip plating for 1 minute until zinc ash and carbide floated on the surface of the zinc liquid, taken out and cooled in a water bath to obtain high adhesion and corrosion-resistant hot-dip galvanized iron components.
[0046] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0047] Zinc chloride 80g / L, zinc acetate 120g / L, acetic acid 30g / L, cyclodextrin 20g / L.
[0048] The preparation method of the plating-assisting solvent is as follows: adding cyclodextrin into 45°C hot water to dissolve evenly, then sequentially adding zinc chloride, zinc acetate and acetic acid to stir and dissolve evenly, and cooling to obtain the plating-assisting solvent.
[0049] Example 4
[0050] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0051] The iron components were sprayed with 40°C alkaline degreasing agent solution (BONDERITE C-AK 338L) for alkaline washing and degreasing treatment, rinsed with water, immersed in 35g / L dilute hydrochloric acid solution for 10 minutes for pickling and rust removal, rinsed with water, immersed in a plating solvent, and treated with plating at 55°C for 90s. After being taken out, they were dried at 120°C for 3min, and then immersed in 490°C hot-dip galvanizing liquid (composed of 0.18wt% aluminum and 98.2wt% zinc) for hot dip plating for 1min until zinc ash and carbides floated on the surface of the zinc liquid. After being taken out, they were cooled in a water bath, and then immersed in a chromium-free passivation solution for immersion passivation treatment for 90s. After being taken out, they were dried and cured at 80°C for 2min to obtain high adhesion and corrosion-resistant hot-dip galvanized iron components.
[0052] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0053] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, cyclodextrin 10g / L.
[0054] The preparation method of the plating-assisting solvent is as follows: cyclodextrin is added into water to be uniformly dissolved, and then zinc chloride, zinc acetate and acetic acid are added in sequence to be stirred and uniformly dissolved to obtain the plating-assisting solvent.
[0055] The chromium-free passivation solution is an aqueous solution containing the following concentration components:
[0056] Water-based acrylic resin emulsion (Dongguan Taikang Polymer Technology Co., Ltd.) 12% (in terms of solid content), silica sol (in terms of SiO2 content) 5%, nickel nitrate 3.5%, triethanolamine borate 3%, citric acid 2.5%, 3-(2,3-epoxypropoxy)propyltriethoxysilane 1%.
[0057] Example 5
[0058] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component comprises the following steps:
[0059] The iron components were sprayed with alkaline degreasing agent solution (BONDERITE C-AK 338L) at room temperature for alkaline washing and degreasing treatment, rinsed with water, immersed in 50g / L dilute hydrochloric acid solution for 5 minutes for pickling and rust removal, rinsed with water, immersed in a plating solvent for 5 minutes at 45°C, taken out and dried at 120°C for 3 minutes, then immersed in 480°C hot-dip galvanizing liquid (composed of pure zinc) for hot dip plating for 1 minute until zinc ash and carbide floated on the surface of the zinc liquid, taken out and cooled in a water bath, then immersed in a chromium-free passivation solution for immersion passivation treatment for 90 seconds, taken out and dried at 80°C for 2 minutes to obtain high adhesion and corrosion-resistant hot-dip galvanized iron components.
[0060] The plating-assisting solvent is an aqueous solution containing the following concentration components:
[0061] Zinc chloride 150g / L, zinc acetate 60g / L, acetic acid 10g / L, cyclodextrin 5g / L.
[0062] The preparation method of the plating solvent is the same as that in Example 1.
[0063] The chromium-free passivation solution is an aqueous solution containing the following concentration components:
[0064] Waterborne epoxy resin emulsion (Shandong Ruisan Chemical Technology Co., Ltd.) 8% (in terms of solid content), silica sol (in terms of SiO2 content) 6%, potassium nitrate 4%, triethanolamine borate 3%, propionic acid 2%, and 3-aminopropyltriethoxysilane 1%.
[0065] Comparative Example 1
[0066] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0067] Zinc chloride 120g / L, ammonium chloride 120g / L.
[0068] The preparation method of the plating-assisting solvent is as follows: zinc chloride and ammonium chloride are added into water and stirred to be uniformly dissolved to obtain the plating-assisting solvent.
[0069] The rest is the same as Example 1.
[0070] Comparative Example 2
[0071] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0072] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L.
[0073] The preparation method of the plating-assisting solvent is as follows: zinc chloride, zinc acetate and acetic acid are added into water and stirred to uniformly dissolve to obtain the plating-assisting solvent.
[0074] The rest is the same as Example 1.
[0075] Comparative Example 3
[0076] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0077] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, chitosan 10g / L.
[0078] The preparation method of the plating-assisting solvent is as follows: acetic acid is added into water to be uniformly dissolved, and then chitosan, zinc chloride and zinc acetate are sequentially added and stirred to be uniformly dissolved to obtain the plating-assisting solvent.
[0079] The rest is the same as Example 1.
[0080] Comparative Example 4
[0081] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 1, the plating-assisting solvent is an aqueous solution containing the following concentration components:
[0082] Zinc chloride 120g / L, zinc acetate 90g / L, acetic acid 20g / L, surfactant OP-10 10g / L.
[0083] The preparation method of the plating-assisting solvent is as follows: adding the surfactant OP-10 into water and dissolving it uniformly, then sequentially adding zinc chloride, zinc acetate and acetic acid and stirring and dissolving them uniformly to obtain the plating-assisting solvent.
[0084] The rest is the same as Example 1.
[0085] The galvanized layer thickness (magnetic thickness gauge detects 10 different sites and takes the average value), adhesion (refer to Appendix L of DL / T5358-2006, thermal spray coating bonding strength test method, observe with a 4x magnifying glass, no coating peels off from the substrate, proving good adhesion), coating uniformity (refer to Appendix A of GB / T2694-2018 hot dip galvanizing layer uniformity test, copper sulfate test method, record the number of corrosion resistance), corrosion resistance (refer to GB / T10125, artificial atmosphere corrosion test salt spray test, acetic acid salt spray (AASS) after 240h, percentage of corrosion area to total area) and zinc loss rate (mainly zinc ash and bottom slag loss, calculated as: total weight of consumed hot dip galvanizing liquid-actual galvanizing layer calculated weight / total weight of hot dip galvanizing liquid) of the galvanized iron components obtained in the above Examples 1 to 3 and Comparative Examples 1 to 4 were tested, and the smoke generation during the hot dip galvanizing process was observed. The results are shown in Table 1 below.
[0086] Table 1
[0087]
[0088]
[0089] It can be seen from the results in Table 1 that the use of the plating solvent of the present invention can significantly improve the uniformity and corrosion resistance of the coating, and can significantly reduce the zinc loss rate and significantly reduce the generation of hot-dip galvanizing smoke compared to conventional zinc chloride and ammonium chloride plating solvents. In addition, it can be seen from the results of Comparative Examples 2 to 4 that the addition of cyclodextrin has a very significant effect on improving the uniformity and corrosion resistance of the coating, and can further reduce the zinc loss rate. Compared with conventional surfactants and crystallization film-forming aids such as chitosan, the use of cyclodextrin as a crystallization film-forming aid in the present invention has obvious advantages.
[0090] Comparative Example 5
[0091] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 4, the chromium-free passivation solution does not contain silica sol and 3-(2,3-epoxypropoxy)propyltriethoxysilane components, and the rest is the same.
[0092] Comparative Example 6
[0093] A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component. Compared with Example 5, the chromium-free passivation solution does not contain silica sol and 3-aminopropyltriethoxysilane components, and the rest is the same.
[0094] The corrosion resistance of the galvanized iron components obtained in the above Examples 4 to 5 and Comparative Examples 5 to 6 was tested, and the results are shown in Table 2 below.
[0095] Table 2
[0096] Test sample Example 4 Example 5 Comparative Example 5 Comparative Example 6 Corrosion resistance 3.7% 4.3% 5.9% 6.6%
[0097] It can be seen from the comparison results of Examples 4-5 in Table 2 with Examples 1-2 in Table 1 that the use of the chromium-free passivation solution of the present invention to passivate the iron components after hot-dip galvanizing can further improve their corrosion resistance. It can be seen from the results of Examples 4-5 and Comparative Examples 5-6 that the addition of silica sol and silane coupling agent has a significant effect on improving the corrosion resistance of the chromium-free passivation solution. The reason is that the addition of silica sol and silane coupling agent can form SiO2 and organic silicon composite film layers with excellent corrosion resistance and water resistance in the aqueous film-forming resin.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component, characterized in that: The steps include: The iron component which has been subjected to alkaline degreasing treatment, pickling and rust removal treatment, and water rinsing treatment is immersed in a plating solvent, and the plating treatment is carried out at a temperature of 40-70°C for 30s-5min, and then taken out and dried, and then immersed in a hot-dip galvanizing solution for hot-dip plating, and then taken out and cooled to obtain a high-adhesion and corrosion-resistant hot-dip galvanized iron component; The plating-assisting solvent is an aqueous solution composed of the following concentration components: Zinc chloride 80~150g / L, zinc acetate 60~120g / L, acetic acid 10~30g / L, cyclodextrin 5~20g / L; The hot-dip galvanizing liquid is pure zinc liquid or zinc liquid added with trace elements; the trace elements are at least one of rare earth elements, aluminum, silicon, and tin; the amount of the trace elements added is 0.1% to 5% of the mass of the zinc liquid; The temperature of the hot-dip galvanizing is 450-550°C.
2. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 1, characterized in that: The alkaline degreasing treatment refers to spraying the iron components with an alkaline degreasing agent solution at 20-60°C for alkaline degreasing treatment; the acid washing and rust removal treatment refers to immersing the iron components in a 20-50g / L dilute hydrochloric acid solution for 5-15 minutes.
3. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 1, characterized in that: The drying refers to drying at 100-150° C. for 2-10 minutes.
4. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 1, characterized in that: The hot-dip galvanized iron component is further immersed in a chromium-free passivation solution for passivation treatment to obtain a high-adhesion, corrosion-resistant hot-dip galvanized iron component; the chromium-free passivation solution is an aqueous solution containing the following concentration components: Water-based resin film-forming agent 5%~15%, silica sol 3%~8%, nitrate 2%~5%, corrosion inhibitor 2%~5%, organic acid 1%~5%, silane coupling agent 0.5%~2%.
5. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 4, characterized in that: The water-based resin film-forming agent is a water-based acrylic resin, a water-based polyurethane, a water-based silicone resin or a water-based epoxy resin.
6. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 4, characterized in that: The nitrate is at least one of sodium nitrate, potassium nitrate, aluminum nitrate, magnesium nitrate, nickel nitrate, cobalt nitrate and cerium nitrate; and the corrosion inhibitor is a phosphate corrosion inhibitor or a borate corrosion inhibitor.
7. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 4, characterized in that: The organic acid is at least one of phytic acid, citric acid, tartaric acid, acetic acid, propionic acid and butyric acid.
8. The method for preparing a high-adhesion, corrosion-resistant hot-dip galvanized iron component according to claim 4, characterized in that: The silane coupling agent is at least one of an alkyl silane coupling agent, a vinyl silane coupling agent, an epoxy silane coupling agent, and an amino silane coupling agent.
Citation Information
Patent Citations
Multifunctional plating assistant agent used for hot dipping
CN101575691A
Hot galvanizing flux and hot galvanizing technological method
CN110172658A
Plating assistant solution and hot galvanizing process using same
CN112126876A
Hot galvanizing process for iron-based casting
CN116219344A